2019
DOI: 10.5114/hivar.2019.88475
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of peer education interventions on HIV- and HBV-preventive behaviours in women with substance-related disorders: a cluster randomised control trial

Abstract: Introduction: Substance-related disorders (SRDs) have become a problematic phenomenon in many countries, including Iran. Risky sexual behaviours are highly prevalent among people with SRDs. This study aimed to evaluate the effectiveness of a peer education program on preventive behaviours related to human immunodeficiency virus (HIV) and hepatitis B virus (HBV) in women with SRDs. Material and methods: One hundred eligible female drug abusers from 10 drop-in centres located in Tehran were entered into the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…About half (8 of 17) of the health promotion and education interventions were found to have positive results [ 25 , 26 , 38 , 39 , 54 , 56 , 57 , 65 , 66 , 84 ]. Some of these studies also had mixed results.…”
Section: Resultsmentioning
confidence: 99%
“…About half (8 of 17) of the health promotion and education interventions were found to have positive results [ 25 , 26 , 38 , 39 , 54 , 56 , 57 , 65 , 66 , 84 ]. Some of these studies also had mixed results.…”
Section: Resultsmentioning
confidence: 99%
“…However, based on a recent meta-analysis [ 26 ], empirical evidence in LMICs is much more limited. Only 4 studies have been reported so far on the goal of abstinence, including an RCT in Iran [ 27 ], a cohort study in Vietnam [ 28 ], a pilot mixed method study in Malaysia [ 29 ], and a feasibility study in Indonesia, which tested a family-based educational approach for adolescents with SUD delivered by peers [ 30 ].…”
Section: Introductionmentioning
confidence: 99%